Anti-Osteoporotic Effects of the Herbal Mixture of Cornus officinalis and Achyranthes japonica In Vitro and In Vivo - Eunkuk Park; Chang Gun Lee; Jeonghyun Kim; Eunguk Lim; Seokjin Hwang; Seung Hee Yun; Yoonjoong Yong; Hyesoo Jeong; Ji Ae Kim; Hyun-Seok Jin; Seon-Yong Jeong (Plants, 2020)
Osteoporosis is a porous bone disease caused by bone density loss, which increases the risk of fractures. Cornus officinalis (CO) and Achyranthes japonica (AJ) have been used as traditional herbal medicine for various disorders in East Asia. Although the anti-osteoporotic effects of single extract of CO and AJ have already been reported, the synergistic effect of a combined mixture has not been studied. In this study, we investigated the effects of a CO and AJ herbal mixture on osteoporosis in in vitro and in vivo models. The results demonstrate that treatment with the CO and AJ mixture significantly promoted osteoblast differentiation of MC3T3-E1 mouse preosteoblasts through the upregulation of osteoblastic differentiation-associated genes such as alkaline phosphatase (Alpl), runt-related transcription factor 2 (Runx2), and bone gamma-carboxyglutamic acid-containing protein (Bglap), while the mixture significantly inhibited differentiation of osteoclasts isolated from primary-cultured mouse monocytes. In addition, oral administration of CO and AJ mixture significantly prevented bone mineral density loss and trabecular bone structures in an ovariectomy-induced osteoporotic mouse model. These results suggest that the combination treatment of CO and AJ mixture might be a beneficial therapy for osteoporosis.